STRATEGI DALAM KEWIRAUSAHAAN DIGITAL - Wahab Wahab (Prosiding Seminar Nasional Indonesia, 2023)
In this era, technological development is very rapid. The development of artificial intelligence has an impact on economic activities. Web-based applications are also experiencing rapid development, especially in the field of e-commerce which makes business competition stronger and more competitive. The development of information technology helps reach customers and provide the best service, whether for large or small companies, currently requires a digital presence. The massive growth in digital entrepreneurship has been made possible by the availability of a plethora of digital tools and services. The growth of new start-ups in the field of technology makes it easier to find information spread across various channels. The growth of new start-ups has customers waiting and looking for the next best thing so this opens up a lot of room for A new company to be born. Startups need initial financing, such as overhead costs that can be minimized in several ways. Co-working spaces, for example, are becoming common nowadays because they allow you to open your own office without having to own a home.